An Analysis of Buddhamma Approved in Mulakaccayana Text Isan Script - Udomchodnamon, Chaiyasit; Namon, Asst. Prof. Sorut; Rachiwong, Worawat; Pongpha, Dr.Sinmongkhon (Journal for Developing the Social and Community, 2018)
This research aim to analyze the Buddha-dhamma principles existing in Mulakachayana scriptures written in Isarn (Northeastern) Dhamma letter. The objectives including (1) to study the history and content of Mulakachayana scriptures, (2) to study Dhamma principles existing in Mulakachayana scriptures, and (3) to analyze the value of Mulakachayana scriptures written in Isarn (Northeastern) Dhamma letter and its impact on uniqueness and identity of northeast locality as followings document research method using Mulakachayana scriptures of Isan language from WatSalaram Buddhist temple, Laithung sub-district, Trakarnphuedphon district, Ubonratchathani province covered the Pali, Thai and Thai Pali. The scriptures are analyzed in terms of composition, morality, structure, content, composition, idioms, and syllables. For the value of the Book of Mulakachayana. The research results found that; Mulakachayana scriptures was written in ancient isarn letter and ked at Selaran Buddhist temple, Ban borhin, Laithung sub-district, Trakarnphuedphon district, Ubonratchathani province. There are separate for 8 groups. The Buddhist Dhamma consist of; Bodhipakkhiyadhamma: Qualities contributing to enlightment.